Factors influencing implementation of the GLA:D Back, an educational/exercise intervention for low back pain: a mixed-methods study. Issue 4 (10th December 2021) - Ris, Inge; Boyle, Eleanor; Myburgh, Corrie; Hartvigsen, Jan; Thomassen, Line; Kongsted, Alice
ABSTRACT: Introduction and aims: Guidelines for low back pain (LBP) management recommend patient education and exercises. GLA:D Back, a structured group-based patient-education exercise program for LBP, facilitates evidence-based care implementation. This study aimed to inform on the implementation processes, assessing clinician-related factors. Objectives were to describe profiles of implementers and nonimplementers by demographics, and responses to the tailored version of the Determinants of Implementation Behaviour Questionnaire (DIBQ-t) qualitatively explore clinician perspectives on implementation, and compare the results of the DIBQ-t with the interview data to evaluate their fit of integration for facilitators, barriers, and new insights. Methods: A mixed-methods parallel design study was conducted. Physiotherapists and chiropractors, educated in the GLA:D Back program, were asked to complete the DIBQ-t (measuring theoretical determinants of implementation) 6 months after their training. Implementers and nonimplementers of the program were selected for interviews. Qualitative data were used to understand clinicians' viewpoints on implementation, providing a broader perspective on the quantitative data and exploring new aspects. Results: More physiotherapists than chiropractors implemented the program. Implementers responded more positively on most domains of the DIBQ-t. The interviews revealed three themes important for implementation: personal gain, practicalities, and buying-in on the program. Clinicians' attitudes to the program appeared additionally as relevant to implementation. Conclusion: The profession of the clinician was associated with implementation behavior. Implementers and nonimplementers identified the same themes but perceived them as either positive or negative. Both groups reported high levels of knowledge and skills, indicating that training alone is insufficient for implementation.